Synthesis, Spectroscopic Characterisation, and Biopotential and DNA Cleavage Applications of Mixed Ligand 4-N,N-Dimethylaminopyridine Metal Complexes - C. Surendra Dilip; K. Manikandan; D. Rajalaxmi (a) Subahashini; R. Thiruneelakandan (Journal of Chemistry)
The mixed ligand transition metal complexes of 4-N,N-dimethylaminopyridine (DP) and chloride as primary and secondary ligands with the general formula [M(DP)3Cl3]; M = Cr(III) and Fe(III); [M′(DP)4Cl2]M′ = Co(II), Ni(II), Cu(II), and Cd(II) were synthesized in a microwave oven. The complexes were characterized by FT-IR and UV, 1HNMR, 13CNMR spectra, TG/DTG, and various physicoanalytical techniques. From the magnetic moment measurements and the electronic spectral data, a distorted octahedral geometry was proposed for the complexes. The complexes express similar trend of thermal behaviour such that they lose water of hydration initially with the subsequent emission of organic and inorganic fragments and leave left the metal oxides as residue. The activation thermodynamic parameters, such as , , , and of the metal complexes, illustrate the spontaneous formation of the complexes. The antimicrobial studies against various pathogenic bacterial and fungal serums insist on that the enhanced potential of the complexes over their ligand and their biopotential properties increases with concentration. The DNA interaction of the synthesized complexes on CT-DNA was investigated by UV-Vis spectroscopy, viscosity, thermal denaturation, and electroanalytical experiments and their binding constants () were also calculated.